Multi-Angle Polarization Index System for Pollen Type Bioaerosol Recognition - Xu, Qizhi; Zeng, Nan; Guo, Wei; Guo, Jun; He, Yonghong; Ma, Hui (Frontiers in Physics, 2022)
In this work, we propose a high-throughput on-line identification method of bioaerosols based on multi-angle polarization index system (MAPIS). In the study, four categories and ten subclasses of aerosol samples from biological and non-biological sources are detected under three incident polarization mode. Then their measured MAPIS shows that bioaerosols like pollen can be easily distinguished from other types of aerosols. Not only that, experimental results also indicate the feasibility of fine identification between different kinds of bioaerosols based on MAPIS in P and R modes. To further extract simple and optimized polarization characterization parameters suitable for bioaerosols, we analyze the multidimensional data of MAPIS by PCA then validate the aerosol recognition accuracy using the first two principal components by multiple groups of randomly mixed aerosol datasets. The comparison with PCA components based on only scattering intensity demonstrate that MAPIS can be not only applied in the specific identification of bioaerosols, but also suitable for the distinction between different kinds of bioaerosols.